In vitro ruminal biohydrogenation of C18 fatty acids in mixtures of Indigofera zollingeriana and Brachiaria decumbens - Makmur, M.; Zain, M.; Marlida, Y.; Khasrad, K.; Jayanegara, A. (Diponegoro University, 2020)
This research was aimed at studying the in vitro ruminal biohydrogenation (BH) of C18 fatty acids (FA) in mixtures of Indigofera zollingeriana and Brachiaria decumbens. Four combinations of experimental rations of I. zollingeriana : B. decumbens were tested i.e., IZ 1 (45%:45%), IZ 2 (60%:30%), IZ 3 (75%:15%), and IZ 4 (90%:0%). The remaining 10% in in each ration was rice bran. The experimental design was based on a completely randomized design with five replicates. Results revealed that there was a statistically significant difference (P<0.01) in the composition of C18 unsaturated FA (UFA) and saturated FA (SFA) for each in vitro incubation period of 1, 2, 4, 8 and 24 h. The highest accumulation of C18 UFA at 24 h was observed in the incubation of IZ 4 (19.87%). The BH of C18:3, C18:2, and C18:1 showed no differences (P>0.05). Composition of C18:0 after incubation showed a significant difference (P<0.01) with the lowest composition was observed in IZ 2 (22%). In conclusion, combination of I. zollingeriana and B. decumbens at different ratio has minor inhibition effect on BH of C18 UFA.